US-TIP Report: As a Political and Economic Instrument of the United States Government - Temasmico Djayoesman, Erwin (Riviera Publishing, 2025)
International relations is a discipline that studies the interaction between countries from various perspectives, where political and economic dynamics are interrelated and influence global policy. In this context, the US-TIP Report emerged as a strategic instrument that the United States uses to implement soft-diplomacy through an assessment of countries' efforts to combat trafficking in persons. This study aims to analyze the interaction between economic and political factors in the preparation of the US-TIP Report and examine its implications for the foreign policy of the United States. The novelty of the research lies in the integration of interdisciplinary analysis that combines political economy and foreign policy perspectives in examining the use of this report as a political and economic tool. The method used is a descriptive qualitative approach with case study design, through the collection of primary data from in-depth interviews with experts and secondary data from official documents, annual reports, and related academic literature. The results of the study show that the preparation of the US-TIP Report is greatly influenced by political and economic interests, where this report plays a role in pressuring countries with low capabilities and supporting the United States' allies. In conclusion, the US-TIP Report not only reflects the real conditions in the fight against trafficking in persons, but also serves as a strategic political and economic tool that directs the dynamics of international relations through assessments that are political and economic.